2019
DOI: 10.1111/ocr.12263
|View full text |Cite
|
Sign up to set email alerts
|

Compliance monitoring via a Bluetooth‐enabled retainer: A prospective clinical pilot study

Abstract: Structured Abstract Objectives To conduct a prospective pilot trial to test the clinical efficacy and accuracy of a newly developed Bluetooth‐enabled retainer, which was synchronized with an iOS mobile application, cloud database and provider webpage. Setting and Sample Population Five orthodontic residents in a university setting. Material and Methods At the delivery of the retainers (T0), each participant was given an Bluetooth‐enabled retainer, logbook and iPod Touch installed with the mobile application. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…As for retainer wear, most studies tend to focus on patient compliance, the length of retainer wear and the type of retainer prescribed [18][19][20][21][22]. Not many studies have been carried out on the knowledge of retainer wear among orthodontic patients.…”
Section: Discussionmentioning
confidence: 99%
“…As for retainer wear, most studies tend to focus on patient compliance, the length of retainer wear and the type of retainer prescribed [18][19][20][21][22]. Not many studies have been carried out on the knowledge of retainer wear among orthodontic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Castle investigated patient compliance with Hawley-style retainers fitted with Bluetooth data trackers and reported that the patient sample was fairly compliant with regimen instructions. 18 Vagdouti found that there was high patient compliance with Hawley-style and vacuum-formed retainers. They also found that vacuum-formed retainers were better accepted by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Możliwe jest także przesyłanie danych do aplikacji mobilnej w telefonie. Specjalne oprogramowanie komputerowe odczytuje i intepretuje dane [5,7,18,19,20]. Korzystne właściwości fizyczne urządzenia takie jak małe wymiary (13x9x4 mm) i niewielka waga (0,4g) umożliwiają jego integrację z różnymi rodzajami aparatów zdejmowanych, w tym aparatów retencyjnych [21].…”
Section: Wynikiunclassified